VD_FINDINFO HC / 2013 / 46 vom 12. Dezember 2012 - VD Tribunal cantonal (2012)
APPEL EN CAUSE, COMPÉTENCE RATIONE LOCI, LÉGATAIRE, LEGS, COMPÉTENCE INTERNATIONALE | 83 al. 1 let. b CPC, 83 al. 1 let. c CPC, 129 al. 1 LDIP, 86 LDIP